Optimalisasi Kinerja Karyawan Penjualan Melalui Manajemen Beban Kerja (Workload Management): Studi Pada PT. RAS Pekanbaru - Yanus Hulu Septi; teuku reza kurniawan (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research was conducted to determine the effect of Workload on employee performance at PT. RAS Pekanbaru. The population in this study was 32 employees of PT. RAS Pekanbaru in 2024 and the entire population was used as a sample. Data collection techniques in this study were questionnaires, library research and observation. Data analysis in this study used descriptive and quantitative analysis methods. Descriptive is comparing the actual reality with theories that are related to the problem in order to draw a conclusion and tabulated in the form of frequency distribution tables. While the quantitative method in this study is based on data that can be calculated to produce a solid estimate. The results of simple linear regression research in this study are Y = 68.463 - 0,615. By using the t-test, the t_table value is 2,042 and the t_count is 3,711, meaning that t_count > t_table, which means that Workload has a significant effect on employee performance at PT. RAS Pekanbaru with a large influence of 31,5%.